2009
DOI: 10.1186/1757-2215-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone-induced Akt phosphorylation and androgen production are modulated by MAP Kinase in bovine theca cells

Abstract: BackgroundTheca cells play an important role in controlling ovarian steroidogenesis by providing aromatizable androgens for granulosa cell estrogen biosynthesis. Although it is well established that the steroidogenic activity of theca cells is mainly regulated by LH, the intracellular signal transduction mechanisms that regulate thecal proliferation and/or steroidogenesis remain obscure. In this study, we examined whether and how LH controls the PI3K/Akt signaling pathway and androgen production in bovine thec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 37 publications
2
47
0
1
Order By: Relevance
“…This hypothesis is confirmed by the recent finding that the capacity of luteinized granulosal cells isolated from dominant follicles and of luteal cells isolated from CL on day 12 of the estrous cycle to produce progesterone basally and in response to LH are lower for cattle with low versus high AFC ). Moreover, two recent studies showed that LH significantly increased androstenedione production in bovine thecal cells (in accordance with our results), and that addition of two inhibitors of the phosphatidylinositol-3-kinase/Akt signaling pathway significantly decreased LH-induced androstenedione production (Fukuda et al 2009), inhibition of the Akt and Erk pathway inhibited both basal and LH-induced androstenedione secretion by animals) versus high (solid symbols, nZ4) AFC. Animals were synchronized with two injections of PG administered 11 days apart, and blood samples were collected daily from day 6 to 21 of the estrous cycle.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This hypothesis is confirmed by the recent finding that the capacity of luteinized granulosal cells isolated from dominant follicles and of luteal cells isolated from CL on day 12 of the estrous cycle to produce progesterone basally and in response to LH are lower for cattle with low versus high AFC ). Moreover, two recent studies showed that LH significantly increased androstenedione production in bovine thecal cells (in accordance with our results), and that addition of two inhibitors of the phosphatidylinositol-3-kinase/Akt signaling pathway significantly decreased LH-induced androstenedione production (Fukuda et al 2009), inhibition of the Akt and Erk pathway inhibited both basal and LH-induced androstenedione secretion by animals) versus high (solid symbols, nZ4) AFC. Animals were synchronized with two injections of PG administered 11 days apart, and blood samples were collected daily from day 6 to 21 of the estrous cycle.…”
Section: Discussionsupporting
confidence: 78%
“…Recent evidence shows that LH significantly increases CYP17A1 mRNA expression in thecal cells (Fukuda et al 2009), and in this study, it was shown that CYP17A1 mRNA expression was higher in thecal cells from cattle with a high AFC, despite lower basal and episodic LH secretion ). Therefore, the reduced androgen production in animals with a low AFC could be due to an alteration in LH signaling which, in turn, may alter CYP17A1 mRNA expression.…”
Section: Discussionmentioning
confidence: 74%
“…Previously, these pathways have been shown to be involved in the regulation of ovarian functions such as gene expression of key steroidogenic genes [33,34]. Furthermore, cross talk between the Akt/PKB and Erk1/2 pathways had been previously described in several cell types [35].…”
Section: Discussionmentioning
confidence: 99%
“…AKT (Fig. 2) becomes phosphorylated in the follicular cells in rat and bovine species following LH treatment (Carvalho et al 2003, Fukuda et al 2009). …”
Section: Cell Signalingmentioning
confidence: 99%